(untitled) (Revista da Tulha, 2015)
Genus, the word comes from the Latin from which our term gender means family, race. This level of “kinship” that certain musical discourses have with each other has sparked discussions ranging from the evaluation criteria to the relevance of such classification. In this work, a literature review of the first discussions will be made on the genres, especially the treatise on rhetoric Aristotle, continuing with the Latin update by Cicero. In this way, the aim is to have well-established parameters to consider how these categorizations were formed throughout the history of music, until the sociological interfaces that originated the idea of market genres.